Clinicopathological correlation and prognostic significance of VEGF-A, VEGF-C, VEGFR-2 and VEGFR-3 expression in colorectal cancer - Martins, Sandra (2013)
BACKGROUND: Colorectal cancer (CRC) is the third most common type of cancer and the fourth most frequent cause of cancer death. Literature indicates that vascular endothelial growth factor is a predominant angiogenic factor and that angiogenesis plays an important role in the progression of CRC. PATIENTS AND METHODS: The present series consisted of tissue samples obtained from 672 patients who had undergone large bowel resection between 2005 and 2010 at the Braga Hospital, Portugal. Archival paraffin-embedded CRC tissue and normal adjacent samples were used to build up tissue microarray blocks and VEGF-A, VEGF-C, VEGFR-2 and VEGFR-3 expression was immunohistochemically assessed. RESULTS: We observed an overexpression of VEGF-C in CRC when tumour cells and normal-adjacent tissue were compared (p=0.004). In tumour samples, VEGF-C-positive cases were associated with VEGFR-3 expression (p=0.047). When assessing the correlation between VEGF-A, VEGF-C, VEGFR-2 and VEGFR-3 expressions and the clinicopathological data, it was revealed that VEGF-A positive cases were associated with male gender (p=0.016) and well-differentiated tumours (p=0.001); VEGF-C with colon cancers (p=0.037), exophytic (p=0.048), moderately-differentiated (p=0.007) and T3/T4 (p=0.010) tumours; VEGFR-2 with invasive adenocarcinoma (p=0.007) and VEGFR-3 with the presence of hepatic metastasis (p=0.032). Overall survival curves for CRC were statistically significant for rectal cancer, VEGF-C expression and stage III (p=0.019) and VEGFR-3 expression and stage IV (p=0.047). CONCLUSION: Quantification of VEGF-A, VEGF-C, VEGFR-2 and VEGFR-3 expression seems to provide valuable prognostic information in CRC and the correlation with clinicopathological data revealed an association with characteristics that contribute to progression, invasion and metastasis leading to poorer survival rates and prognosis.